2013
DOI: 10.7763/ijcea.2013.v4.322
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and Phenols of Organically and Conventionally Cultivated Potato Varieties

Abstract: Abstract-Many of the compounds present in potato are important because of their beneficial effects on health, therefore, are highly desirable in the human diet. The orange and yellow colour of the tuber flesh is due to carotenoids. The aim of this research was to determine the content of total phenolic content and carotenoids in relationship with the colour of organically and conventionally cultivated potato varieties before and after period of storage. In the research 31 potato samples of 12 potato varieties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…Accordingly, a study of 74 Andean potato landraces found about an 11‐fold variation in TSP values . Despite the fact that published data vary widely, those measured by the Folin–Ciocalteu method usually show lower value range from 0.0200 to 1.00 g GAE kg −1 FW due to the limits of the method compared to the Fast Blue method used in this study . Our results are in agreement with previous works reporting higher TSP values in coloured potato tubers; for instance, Madiwale found TSP levels about 0.250 and 2.87 g GAE kg −1 FW, while Stushnoff et al reported values between 0.900 and 4.00 g GAE kg −1 FW in a collection of coloured accessions.…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, a study of 74 Andean potato landraces found about an 11‐fold variation in TSP values . Despite the fact that published data vary widely, those measured by the Folin–Ciocalteu method usually show lower value range from 0.0200 to 1.00 g GAE kg −1 FW due to the limits of the method compared to the Fast Blue method used in this study . Our results are in agreement with previous works reporting higher TSP values in coloured potato tubers; for instance, Madiwale found TSP levels about 0.250 and 2.87 g GAE kg −1 FW, while Stushnoff et al reported values between 0.900 and 4.00 g GAE kg −1 FW in a collection of coloured accessions.…”
Section: Discussionsupporting
confidence: 90%
“…Colored-flesh potatoes get their color from various pigments, which are antioxidants. Purple and rose-flesh potatoes contain the anthocyanin Foods 2020, 9, 1862 2 of 12 pigments, while yellow-colored flesh varieties contain carotenoids [6]. Purple-fleshed potatoes like Blue Congo get their color from common anthocyanins malvidin, peonidin, delphinidin, cyanidin, and petunidin [7].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it can produce more protein and carbohydrates per unit area than cereals and some leguminous crops like soybeans (Guchi 2015). In addition to energy and quality protein, it also provides a substantial amount of vitamins and minerals (Mpogole 2014, Abamecha 2013, Giordanengo et al 2013, Murniece et al 2013, Scott and Suarez 2011.…”
mentioning
confidence: 99%